Integrating Family Strengths in Child Protection Goals - Rijbroek, Brigit; Strating, Mathilde M. H.; Huijsman, Robbert (Child & family social work, 2025)
ABSTRACT Over the last decades, child protection workers (CPWs) have largely focused on improving their work with a strength‐based approach in order to empower families. This study investigates to what extent CPWs draw on families' strengths, that is, by promoting autonomy and competencies and by involving their informal networks in goal formulation. This quantitative study analysed the goals, as stated in case files, formulated by CPWs for 177 families within a single Dutch child protection service. 48.6% of CPWs prioritise promoting families' autonomy in goal formulation. With regard to competencies, only 40.1% of the goals refer to the families' competencies. In addition, the support system that the goals call upon tends to be dominated by formal rather than informal networks (in 71.2% of cases). While it is true that child protection cases can benefit from the support of a formal networks, CPWs overwhelmingly failed to encourage support from existing informal networks (in 95.5% of cases). There were no relationships between these percentages and the nature of the family problems or the question of whether or to what extent the CPWs identified the specific strengths of families. These findings show that half of the CPWs had integrated a strength‐based approach in their daily practice to some extent, and therefore improvements are needed in order to more successfully encourage families to change.